Trajectories of Parental Warmth and the Role They Play in Explaining Adolescent Prosocial Behavior - Buckley, Lisa; Atkins, Tiffany; Perera, Withanage; Waller, Michael (My University, 2023)
Adolescent prosocial behavior suggests social competence and it is associated with greater parental warmth yet the experience of warmth through child and adolescent development is not well understood as it relates to such prosocial behavior. A nationally representative dataset from the Longitudinal Study of Australian Children cohort was used. The analyses involved multiple waves beginning when children were aged 4-5. The main analyses used a sample of 2723 adolescents aged 16-17 years (Mean, S.D. = 16.45, 0.50; 49.2% female, 50.8% male). Parental warmth trajectories (from ages 4-5 through 16-17 years) were created and used to explore the accumulated effect of a lifecourse of parental warmth on adolescent prosocial behavior as measured when adolescents were aged 16-17 years. There were three trajectories described as, consistent (28.7%), slight decline (51.4%), and declining warmth (19.8%). These were associated with prosocial behavior; adolescents with a slight decline in warmth were 2.2 times less likely than those with consistent warmth to have the highest prosocial behavior. Consistent parental warmth likely provides greatest benefit for increased prosocial behavior in mid-adolescence.
Journal of Youth and Adolescence
Keywords: Adolescent; Parent; Parental Warmth; Prosocial; Trajectory; Childhood and child development; Social engagement